Narrativas de experiências profissionais de docentes de educação física no ensino técnico integrado do Institudo Federal de Educação, Ciência e Tecnologia do Espírito Santo - Mendonça, Gilberto Cabral de (2016)
This research seeks to analyze and interpret the professional experience of teachers of Physical Education of the Federal Institute of Science Education and Technology of the Holy Spirit (IFES), considering from initial and continuing education to current teaching practices in physical education classes in integrated technical education. As regards the theoretical and methodological orientation, the research was based on ethnomethodology which contributed to better understanding the actions and interactions mobilized by teachers, based on their professional experience. For this, it used as a tool for individual narrative interview with fieldwork. Hereby, was interviewed seven teachers, which made it possible to identify professional experiences built from the initial training, through continued training throughout the teaching career. Include experiences built on transition from work earlier and now as a professional IFES. Through the transcripts of the interviews, it was possible to set up five axes of analysis: the place of experience in teaching; passion for teaching; the context of the Federal Institute of the Holy Spirit in the formation of teachers' identities; the sport; integrated technical education. Based on the theories of sociology of teacher training experience, teacher identity, the integrated high school and Physical Education in this context, the analysis of the data showed that the experience before entering the IFES, and even the initial training process, are very different. Continuing education is striking for teachers and gives from the needs arising in the teaching practice. The most frequent experiences are in the sport, a fact that remains relevant in integratedtechnical education institution, both with regard to the choices and prioritization process of physical education content, according to the importance assigned to it, as in relations with the projects developed in teaching, research and extension. The trajectories related to sports experiences, pointed out by teachers are the most important in his career. However, the pedagogical treatment differs among teachers, which demonstrates an interest in the sport work in a perspective that goes beyond the technical rationality of education. The experiences go through other functions beyond the traditional classroom, go through different positions as general direction, educational management and coordination, which extends the knowledge of the institution. It appears also that there is great difficulty in working Physical Education in the proposed integrated technical education, difficulty also identified in other areas of knowledge at the Federal Institute of the Holy Spirit. It follows, then, that the most significant professional experiences of physical education teachers in the integrated technical education in IFES are in the context of sport. Other administrative functions in the institution also mark the trajectory of teachers. The integration between high school and vocational education remains a major challenge for the Federal Institute of the Holy Spirit.